2008
DOI: 10.1016/j.cellbi.2008.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced expression of transgene in CHO cells using matrix attachment region

Abstract: The expression of transgenes in mammalian cells is often at a low level mainly due to position effects from the neighboring chromatin context. To improve this, we have constructed a vector pCAM, which contains chloramphenicol acetyltransferase (CAT) reporter gene cassettes, driven by SV40 early promoter and flanked by two human beta-globin MARs in cis. We transfected this vector into the Chinese hamster ovary (CHO) cell line, and found that the level of CAT gene expression with MAR was effectively increased, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
2
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 20 publications
0
30
2
2
Order By: Relevance
“…The FVII expression amount in the selected CHO-K1 cell line was determined to be approximately 300 ng/mL. These results suggest that the construction of vectors (Girod et al, 2005;Wang et al, 2008) should be used in future research to increase the copy number in CHO-K1 cells and thereby improve expression levels.…”
Section: Discussionmentioning
confidence: 95%
“…The FVII expression amount in the selected CHO-K1 cell line was determined to be approximately 300 ng/mL. These results suggest that the construction of vectors (Girod et al, 2005;Wang et al, 2008) should be used in future research to increase the copy number in CHO-K1 cells and thereby improve expression levels.…”
Section: Discussionmentioning
confidence: 95%
“…Other studies have demonstrated that MARs could improve the levels of transgene expression and decrease the transformant-totransformant variations in transgene expression in both plants and animals (Kim et al, 2004;Wang et al, 2008;Zahn-Zabal et al, 2001). MAR sequences from different sources have different gene expression levels (Brouwer et al, 2002;Cheng et al, 2001;Neznanov et al, 1996;Vain et al, 1999;Zhong et al, 2004).…”
Section: Introductionmentioning
confidence: 95%
“…Human β‐globin MAR enhances recombinant gene expression, but the enhancing effects could only be detected in the full‐length fragments (regardless of the orientation); the constructs that contained the minimal sequences of putative MAR (739–1824 and 1135–1472) were not sufficient for enhancing transgene expression (Kim et al, 2004). However, deletion of the human β‐globin MAR DNA fragment from 904 to 1656 can enhance transgenic expression (Wang et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…In order to achieve the cloning orientation, the BglII/KpnI (GTCAGATCT; AGCGGTACC) and SalI/BamHI (GTCGTCGAC; GTCGGATCC) enzyme sites (underlined) with three additional nucleotides were inserted at the 5′ site of the above primers respectively. The amplified MAR fragments were cloned into the pCAG vector to generate the pCAM5, pCAM3 and pCAM vectors, which contained MAR at the 5′ site, 3′ site and both MARs flanking the reporter gene cassettes (Wang et al, 2008). The constructs are shown schematically in Figure 1.…”
Section: Methodsmentioning
confidence: 99%